Combined healthy lifestyle factors and psychosocial outcomes among cancer survivors: a systematic review and meta-analysis - Zhu, Chunsu; Lian, Zhiwei; Arndt, Volker; Thong, Melissa S. Y. (Journal of cancer survivorship, 2024)
This systematic review aims to summarize the associations between combined healthy lifestyles and psychosocial outcomes (health-related quality of life (HRQOL), depression, anxiety, psychological distress (PD), and posttraumatic stress disorder (PTSD)) among cancer survivors.